Radiation, a two-edged sword: From untoward effects to fractionated radiotherapy. (January 2021) - Chew, M.T.; Jones, B.; Hill, M.; Bradley, D.A.
Abstract: Radiations in medicine cover a wide range of applications, predominantly in diagnostic imaging and radiotherapy, encompassing photons (x- and γ-rays) and particle radiation, as well as with the use of liquid sources in nuclear medicine focusing on physiological functional imaging, tumour detection or targeted radiotherapy. The biological interactions of ionizing radiation leads naturally to questions of benefits and risk following dose exposures. The inherent properties of ionizing radiation in sterilising dividing cells can offer immense benefits with respect to tumour control, but radiation can also deliver potential harm in the form of normal tissue toxicity or carcinogenesis. The advances in radiation technology, offering accurate and reliable dose delivery, in concert with greater understanding of the underpinning radiobiological effects are creating an ever-growing ability to extract maximum benefit and minimise risk. The radiobiological effects fall broadly under the headings of mutagenesis, chromosomal aberrations, radiation induced genomic instability and cell death. The enormity of evidence derived from these underlie the mechanism of the six Rs of controlled radiotherapy: repair, repopulation, reoxygenation, redistribution, radiosensitivity and most recently, remote bystander cellular effects (including low dose hyper-radiosensitivity, adaptive response, hormesis, abscopal effect and immune response). Herein, we seek to discuss how such understanding leads to optimised radiotherapy. Highlights: Radiation in medicine is used primarily for diagnosis and radiotherapy. Ionizing radiation beneficial and detrimental effects. The 6 Rs of radiotherapy.